Pierwsza konferencja Henri Lacordaire’a w katedrze paryskiej - Panuś, Kazimierz (Studia Pastoralne, 2026)
The famous „les Confèrences de Notre-Dame” also known as „les Confèrences de Carême” are still very important for the religious life in France. They are addressed to the intelligence and delivered on all Sundays of the Lent in the Notre-Dame in Paris. The beginning was initiated by Henri Dominique Lacordaire (1802–1861), one of the greatest French preachers. The article presents the beginning of the work and analyses the first conference given by Lacordaire on 8 March 1835. The first full Polish translation of the conference is attached to the article because only fragmentary translations of the conference have been known before.